Ferulago longistylis boiss bitkisinden antimikrobiyal aktivite yönlendirmeli etken madde izolasyonu - Günaydın, Burcu (My University, 2017)
Antimikrobiyal aktivite tayinine göre en iyi etkiyi gösteren diklorometan ekstresinden piranokumarin yapısında grandivitin ve aegelinol isimli kumarin bileşikleri izole edildi. ABSTRACTIn the pyranocoumarin structure from the dicholoromethane extract showing the most effect according to antimicrobial activity assay, which are named as grandivittin and aegelinol, coumarin compounds were isolated.
Keywords: Aegelinol; Antimicrobial; Antimikrobiyal; Antioksidan; Antioxidant; Bitkiler; Farmakognozi; Ferulago longistylis; Grandivitin.Ferulago longistylis; Grandivittin